PENGEMBANGAN BERAS ANALOG SIBON (SINGKONG, ABON AYAM) PENGGANTI BERAS PADI - Mufidah, Lina; Eka Rachmawati; Titik Sulistyani (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to develop analog rice from cassava and chicken floss(SIBON). This research uses a mixed approach with research anddevelopment (RnD) types. The research procedure uses 4D which is adoptedinto 3D, namely define, design, and development. This research was conductedat the Culinary Arts Laboratory in March 2024. The subject of this researchwas SIBON rice, namely analog rice from cassava, shredded, and corn starch.The research instrument used in this development research is a panelistquestionnaire which will assess the organoleptic test so that acceptance dataon aspects of aroma, color, taste, and texture are known. Data analysis wascarried out using organoleptic analysis. The parameters analyzed includecolor, texture, smell, and taste. Data analysis uses descriptive analysis. Theresults of the research showed that the organoleptic test results for the tasteaspect were found to be savory, the color aspect was quite brown, the textureaspect was said to be quite chewy, and the aroma aspect was found to be quitefragrant with mocaf in the rice product.